Strategi Penyaluran Pembiayaan Usaha Mikro Kecil Dan Menengah Di Bank Syariah Mandiri : (Studi Bank Syariah Mandiri Kantor Cabang Pasuruan) - Rachmad Nor Firman; Ismatul Azizah (Tasharruf : Journal of Islamic Economics and Business, 2020)
This study aims to determine the financing distribution strategy for micro, small and medium enterprises (MSMEs) at Bank Mandiri Syariah Pasuruan Branch Office. The research method used is descriptive qualitative analysis research method with technical data analysis used is phenomenological analysis. The results of the study resulted in several conclusions, namely first, in the distribution of MSME financing, Bank Syariah Mandiri divided into several segments, namely the fixed income group customer segment, business customer segment, community segment and regional segment. Second, the strategies implemented in the distribution of MSME financing are market penetration strategies or marketing, product manual strategies, strategies for cooperating with agencies, walk-in and existing customer strategies and promotion strategies. Then there are several obstacles from the distribution of MSME financing